The subjective change in the "Poema del manicomio" by Carlos Oquendo de Amat (Revista Innova Educación, 2019)
The objective was to interpret the "Poem of the Asylum" by Carlos Oquendo de Amat from the perspective of discourse analysis. The investigation is located within the qualitative approach and as a method the hermeneutics was used, based on the description and the reflection. The interpretation technique was the discourse analysis in its textual, semiotic, enunciative and pragmatic dimensions. As a general result, it is shown that in the poem the subjective change of the lyrical subject is described, at the personal level of the subject.
Keywords: Subjective change; pragmatic; semiotic; text; enunciation; poem